A produção do espaço urbano pela igreja católica em Uiraúna, PB - Oliveira, Maria Alanya da Costa (Universidade Federal Rural do Semi-Árido, 2017)
The presence of the Catholic Church in Brazil as a colony stood out not only in the religious, but also in the political, social and urban areas, serving as a landscape reference in colonial cities and as responsible for the founding of towns and villages, as is the case in some municipalities From the backlands of Paraiba. This work had as objective to understand how the Catholic Church interfered in the process of urban development in the city in question since it was around her that the municipality flourished and developed, analyzing and mapping the parceling of the soil and extension of urban ecclesiastical lands that still Remain until the present day in the conformation of space. With the system of sesmarias, where lands were donated for purposes of occupation and exploration, the church was instrumental in attracting people to its surroundings. With this, the location of these lands gave conditions to the Church in deciding on the development of small villages, predominantly in its surroundings becoming later the centers of the cities. In the municipality of Uiraúna this was no different, the city was born and grew up around the small chapel, where donations of land paved the way for urban expansion mainly because of the ideological and dominant character of the Catholic faith. The methodology used was divided into: a) Bibliographic survey, search of old photographs and maps. B) Documentary research, collection of official documents acquired in the parish secretariat. C) Field study, observation of the landscape to verify the vestiges of past times and the relation with the urban layout. According to the history of the ancient inhabitants, by the local parish priest, as well as by the ecclesiastical records itself, it was found that the village of Uiraúna came from the elevation of a chapel built on land donated by a local farmer. It was not possible to identify the date when the town was elevated to the village, but it was in 1953 that the administrative political interest of a political chief, along with the contribution of a state deputy, managed to elevate the village to the city of Uiraúna. Therefore, it is hoped that this work contributed to the study of small cities in relation to the production of the Uranian space, and that other themes may arise in order to further deepen this historical element.
Keywords: Cidades; Cities; Igreja Católica; Catholic Church; Sesmarias; Sesmarias; Terras Urbanas; Urban Land; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA